The "higher criticism" and the verdict of the monuments - Sayce, Archibald Henry, 1845-1933 (London, UK Societyfor Promoting Christian Knowledge, 1901)
Includes index.
First edition published 1893. Donated by the late Thomas C. Denton.
Keywords: Bible -- historical criticism